Pengaruh Penggunaan Media Tanam Terhadap Brix dan Uji Organoleptik Tanaman Mentimun Jepang (Cucumis sativus var. Japonese) Dengan Hidroponik Sistem Drip - Azzahra, Fadila Kamilia; Hidayati, Irul; Faizah, Hanik (Biosel Biology Science and Education, 2024)
The Japanese cucumber plant is a type of fruit vegetable that is widely consumed by Indonesian people. Japanese cucumber is beneficial for the body as an anti-inflammatory, cooling agent, and even as an anti-cancer. Japanese cucumber planting is done using the hydroponic method. Hydroponics is a method of growing without soil. One system that is effective and efficient in terms of energy and time is the drip system. Drip system hydroponic planting is a system that requires a substrate or planting medium. In this research, several planting media were used, namely soil, fern roots, husk charcoal, and a combination of husk charcoal and fern roots. The aim of this research was to determine the effect of planting media on the Brix and organoleptic tests of Japanese cucumber fruit. The research method used was experimental with a Completely Randomized Design (CRD). The planting media treatments used were Control = soil, P1 = fern roots, P2 = husk charcoal, P3 = husk charcoal: fern roots. Research and observations were carried out for approximately 60 days. Then the data that has been collected is analyzed using the One-Way Anova test. The results showed that the planting medium had no effect on Brix. In the best average Brix parameter obtained P3 (5.100) and in the organoleptic test each criterion shows the best different treatment results, in the color criterion the best treatment is shown by P3 (4.13), the texture criterion is shown by P2 (3.40), and the criteria taste indicated by control (3.47).  Keywords: Brix, Drip, Hydroponics, Japanese Cucumber, Substrate